Enhanced hydrolysis/acidogenesis and potential mechanism in thermal-alkali-biofilm synergistic pretreatment of high-solid and low-organic-content sludge. (June 2023) - Shi, Shuohui; Cao, Meng; Zhang, Ying; Fan, Xing; Liu, Shihu; Chen, Jiahao; Zhou, Jian
Graphical abstract: Highlights: Biofilm assistance improved the performance of thermal-alkali pretreatment. TAB was feasible to treat high-solid and low-organic-content sludge. TAB primarily facilitated solubilization and hydrolysis via stimulated proteolysis. TAB eliminated autochthonous microorganisms in the waste activated sludge. TAB enriched specialized fermentative microorganisms and relevant functional genes. Abstract: Improving the anaerobic digestion (AD) of high-solid and low-organic-content sludge is imperative for sustainable waste activated sludge (WAS) management. Here, a thermal-alkali-biofilm pretreatment (TAB) was established to treat high-solid and low-organic-content sludge and compared with thermal and thermal-alkali methods. The results showed that TAB drastically improved WAS reduction, hydrolysis/acidogenesis efficiency, and biochemical methane potential. TAB possessed the lowest sludge particle size and the highest surface charge due to the stimulated proteolysis and WAS solubilization, supported by the protease activity test and secondary substrate identification. In addition, the biofilm assistance noticeably accelerated the elimination of autochthonous bacteria in WAS (e.g., Proteobacteria) and facilitated the enrichment of specialized fermentative microorganisms (e.g., Firmicutes) along with relevant functional genes, lying molecular foundation for the enhanced hydrolysis/acidogenesis in TAB. These findings could expand the application of biofilm in the AD of WAS and provide new insight into the pretreatment strategy of high-solid and low-organic-content sludge.